2014
DOI: 10.1055/s-0033-1364166
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid Hemorrhage Due to Rupture of an Intracavernous Carotid Artery Aneurysm Coexisting with a Prolactinoma under Cabergoline Treatment

Abstract: We report an unusual case of subarachnoid hemorrhage caused by intraoperative rupture of an intracavernous carotid artery aneurysm coexisting with a prolactinoma. A 58-year-old man presenting with diplopia was found to have a left intracavernous carotid artery aneurysm encased by a suprasellar tumor on magnetic resonance imaging. His serum prolactin level was 5036 ng/mL. Proximal ligation of the left internal carotid artery with a superficial temporal artery to middle cerebral artery anastomosis was scheduled.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…For cUIAs adjacent to brain tumors (Figs. 1, 2), the aneurysm should be treated prior to tumor surgery because the aneurysm may be inadvertently injured and rupture during or after tumor surgery (101112131415). The risk of rupturing a cUIA, especially a large one (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For cUIAs adjacent to brain tumors (Figs. 1, 2), the aneurysm should be treated prior to tumor surgery because the aneurysm may be inadvertently injured and rupture during or after tumor surgery (101112131415). The risk of rupturing a cUIA, especially a large one (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the incidence of cUIA associated with brain tumor ranged from 2.3% to 7.7% (3456789). Considering the variable incidence of cUIA associated with brain tumors (3456789), there are a considerable number of cases in literature documenting perioperative aneurysm rupture (1011121314). This data emphasizes the importance of cUIA management before tumor treatment (121011121314).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 3 There are, however, multiple case reports of SAH from cavernous ICA aneurysms. [4][5][6][7][8] In one report, 4 SAH occurred after the dura was opened during a craniotomy to treat a cavernous ICA aneurysm, which coexisted with a prolactinoma under cabergoline treatment; the authors suggested that an aperture to the subarachnoid space was created by shrinkage of the prolactinoma by cabergoline. We report a case of spontaneous SAH due to rupture of a cavernous ICA aneurysm in a patient whose large prolactinoma had shrunk following cabergoline treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Intracranial aneurysm is found in only 0.3% of brain tumor patients, 9 and a coexisting aneurysm can trigger or exacerbate the disease course of tumors. 10 , 11 Tumors metastatic to the pituitary gland and parasellar aneurysms are usually misdiagnosed as pituitary adenoma. To date, the coexistence of MP and intracranial aneurysms has not been reported in literatures.…”
Section: Introductionmentioning
confidence: 99%